Pancytopenia in a Patient with Rendu-Osler-Weber Syndrome and Uncommon Vascular Abnormalities - Nicolò Binello; Antonio Gasbarrini; Eleonora Gaetani (Case Reports in Hematology)
Rendu-Osler-Weber syndrome, or hereditary hemorrhagic teleangiectasia (HHT), is a rare autosomal dominant vascular disorder, characterized by multiple mucocutaneous teleangiectases with recurrent nasal and gastrointestinal bleedings and/or solid-organ arteriovenous shunts. We describe the first case to our knowledge of pancytopenia in a 53-year-old patient, with a known history of HHT and recurrent nasal and gastrointestinal bleedings, who was found to have a major splenic artery aneurysm and other uncommon vascular abnormalities. In the absence of other evident causes of pancytopenia, hypersplenism was diagnosed. The patient underwent coil embolization of the splenic artery aneurysm, followed by rapid and sustained increase of white blood cell and platelet count. Splenic artery aneurysms are extremely uncommon in HHT as only anecdotal cases have been reported to date. However, we believe that the aneurysm critically contributed to the progression of splenomegaly and the development of pancytopenia.